ANALISIS PENDAPATAN USAHATANI JERUK SIAM DI KECAMATAN CEMPAKA KABUPATEN OGAN KOMERING ULU TIMUR - Henny Rosmawati, Ema Pusvita, Evi Tamala, Putri Ayu Ogari, Windi Lestari, (JASEP, 2025)
Siamese orange is one of the horticultural crops that has good development prospects for cultivation. This study aims to analyze the income of Siamese orange farming in Cempaka District, East OKU Regency. The location was determined purposively considering that Cempaka District is the center of citrus plants in East OKU Regency. The research method used was a survey method. The sampling method used in this study was a saturated sampling method, which took all Siamese orange farmers in Cempaka District, East OKU Regency, totaling 24 farmers. Income obtained from Siamese orange farming was calculated using the income formula. The results showed that the income of Siamese orange farming in Cempaka District, East OKU Regency was Rp 94,195,780/year.